A Comparative Study Of The Financial Performance Of Islamic And Conventional Banks In Peshawar - Hussain, Muhammad; Jan, Sharif Ullah; Haq, Muhammad Zia Ul (Baca Dulu Publisher, 2024)
The research aimed to assess the financial performance of Islamic and Conventional banks in Peshawar between 2006 and 2014. To facilitate comparison, five Islamic banks were matched with five similarly sized conventional banks. The study revealed that Islamic banks outperformed conventional banks in efficiency, return, and asset quality. However, Islamic banks faced challenges in areas such as advances, investment, liquidity, deposits, and capital, where conventional banks showed better performance. Islamic financial institutions often impose higher spreads and allocate a smaller portion of distributable income to depositors in comparison to conventional banks. To enhance credibility and contribute to Islamic socio-economic goals of fairness and equality, it is important for Islamic banks to prioritize equitable profit distribution to depositors. Additionally, these banks should emphasize the creation of novel products and inventive solutions to cater to client demands, while also bolstering their equity foundation.